Study on Zinc-binding Capacity of Featherback (Chitala ornata) Skin Hydrolysate - Vo, Tam Dinh Le; Tran, Thinh Ngoc; Vo, Bao Chi; Ma, Hieu Trung; Tran, Hoa Gia; Nguyen, Son Manh; Hoang, Quyen Phuong; Nguyen, Van Thi Tuyet; Nguyen, Mai Thi Ngoc; Nguyen, Thao Huynh Ngoc; Pham, Vy Thuy; Cao, Khang Tran Gia; Pham, Cuong Viet (Universitas Gadjah Mada, 2025)
This study aims to valorize featherback (Chitala ornata) skin by-product by generating zinc-binding hydrolysate using Alcalase. Commencing with an effective assessment of hydrolysis conditions on the zinc-binding capacity (ZnBC), the hydrolysate gave the highest ZnBC. Subsequently, the hydrolysate was fractionated using ultrafiltration centrifugal devices, analyzed for its amino acid composition, and examined for the stability of its ZnBC against heat and pH. At the best hydrolysis condition, including the skin:water ratio of 1:4 (w/v), enzyme:substrate (E:S) ratio of 40 U/g protein, pH = 8, temperature of 50 °C, and hydrolysis time of 5 h, the gained hydrolysate exhibited the greatest ZnBC of 30.28 ± 0.83% (2.66 folds lower than that of ethylenediamine tetraacetic acid disodium salt (Na2EDTA)) and contained 8 essential amino acids (making 21.12% total amino acids). Besides, the hydrolysate’s ZnBC could retain above 66% after pH treatment in range 1–11 or thermal treatment at 100 °C for 180 min. The < 1 kDa fraction expressed the highest ZnBC of 38.48 ± 2.96%, 2.09 times lower than Na2EDTA. These findings indicate that hydrolysate and/or its peptide fractions derived from featherback skin could be a natural supplement, especially when producing functional food or nutraceuticals.